Colorimetric detection of bisphenol A in food and water based on the laccase-mimicking activity of silver phosphate nanoparticles - Siyu Wu; Jiali Chen; Yue Tang; Yuangen Wu (Food Innovation and Advances)
Bisphenol A widely remains in food and environmental systems. A small amount of bisphenol A can directly affect human health. However, the recent colorimetric detection methods of bisphenol A still meet the challenges such as complex operations and the influence of high-salt solutions, resulting in inaccurate detection results. Herein, Ag3PO4 nanoparticles are prepared through a facile coprecipitation method and have excellent laccase-mimicking catalytic activity. Under the catalytic action of Ag3PO4 nanoparticles, bisphenol A loses electrons and further reacts with 4-amino-antipyrine to form a red substance. Thus, a novel rapid colorimetric method for bisphenol A detection is first established based on the laccase-mimicking activity of Ag3PO4 nanoparticles. The limit of detection of the colorimetric method is determined as low as 0.222 mg·L−1, which is lower than the National Health and Family Planning Commission of China and the United States Food and Drug Administration. Moreover, the colorimetric method displays excellent selectivity against other competitive targets. Further research has confirmed the accuracy, reliability, and rapidity of the colorimetric method for detecting bisphenol A in actual food and water samples, which indicates that such a colorimetric method will play a potentially vital role in practical applications.